Ni-Zn Hydroxide based bi-Phase Multiscale Porous Nanohybrids: Physico-Chemical Properties - N. Habib, O. Guellati, A. Harat, A. Nait-Merzoug, J. El Haskouri, D. Momodu, N. Manyala, D. Begin and M. Guerioune (Applied Nanoscience, 2019)
In this investigation, we report the synthesis of novel homogeneous micro–mesoporous bi-phase nanohybrids based on Ni/Zn hydroxides using a simple and low-cost free-template urea-based hydrothermal process at two different growth temperatures (120 and 180 °C) for 6 h in two cases of precursor ratios (Ni:Zn = 1:1 and Ni:Zn = 1:2). The synthesized products have been characterized with different techniques such as XRD, FT-IR, FESEM, Raman, BET and XPS analysis to identify quantitatively and qualitatively their original physico-chemical properties. The obtained structural results show the formation of bi-hydroxide-based products: α*-Ni(OH)2·0.75 H2O with Zn5(CO3)2(OH)6 (case Ni:Zn = 1:1) or with Zn4(CO3)(OH)6·H2O (Ni:Zn = 1:2) which are also proven by FTIR and Raman analyses. However, the obtained 3D micro–meso-nanohybrids with different pore morphology have been demonstrated through the FESEM micrographs depending on the synthesis conditions. Moreover, these porous products have been subjected to textural studies with the BET results showcasing a porous morphology with a reasonable specific surface area (SSA) and pore volume in the range (70–150 m2/g) and (0.19–0.85 cm3/g), respectively. Also, a clear improvement in the BET SSA (two times the initial value) was obtained with increasing the growth temperature in the two cases (1:1 and 1:2). Consequently, we have successfully synthesized active mesoporous materials with interesting specific surface area and porosity (pore volume and size) which make them attractive materials for electrode applications especially in energy storage and biosensing.